Inside Cover. Issue 5 (24th April 2022) - Ma, Haigang; Wang, Zhiyang; Zuo, Chao; Huang, Qinghua
Abstract : Here, a three dimensional confocal photoacoustic dermoscopy (3D‐CPAD) equipped with an autofocusing sono‐opto probe was developed to facilitate the 3D reconstruction of high‐contrast and high‐spatial‐resolution imaging of human skin with multilaminate structures in depth direction. The autofocusing sono‐opto probe mainly integrated an electrowetting‐based varifocal lens to automatically control the acoustic and optical confocal length, and an annular ultrasonic detector with coaxial configuration for receiving photoacoustic signals. Further details can be found in the article by Haigang Ma, Zhiyang Wang, Chao Zuo, and Qinghua Huang (e202100323 ) Abstract : Here, a three dimensional confocal photoacoustic dermoscopy (3D‐CPAD) equipped with an autofocusing sono‐opto probe was developed to facilitate the 3D reconstruction of high‐contrast and high‐spatial‐resolution imaging of human skin with multilaminate structures in depth direction. The autofocusing sono‐opto probe mainly integrated an electrowetting‐based varifocal lens to automatically control the acoustic and optical confocal length, and an annular ultrasonic detector with coaxial configuration for receiving photoacoustic signals. Further details can be found in the article by Haigang Ma, Zhiyang Wang, Chao Zuo, and Qinghua Huang (e202100323 )